Is Medical Therapy for Distal Ureteral Stones Efficient? Tamsulosin versus Deflazacort: A Prospective Randomised Trial - Kucukpolat, Salim; Kocaaslan, Ramazan; Kadihasanoglu, Mustafa; Bagcioglu, Murat; Kocan, Huseyin; Sarica, Kemal (Aktuelle Urologie, 2019)
Introduction To evaluate the efficacy of tamsulosin and deflazacort in the spontaneous expulsion of distal ureteral stones when applied in an independent or combined manner.Methods 134 patients with distal ureteral stones (4 – 10 mm) were included in tothe study. All patients were randomized into four groups: group 1 (n = 37) patients receiving tamsulosin (0.4 mg/day); group 2 (n = 26) patients receiving deflazacort (30 mg/day); group 3 (n = 37) patients receiving combined treatment (tamsulosin and deflazacort) with the same dosages; and group 4, control group cases (n = 34), receiving paracetamol on demand. Although deflazacort treatment was limited to 10 days due to the possible associated side effects, α-blocker and paracetamol lasted up to four weeks. Patients were followed up on a weekly basis and at the end of four weeks all groups were compared primarily with respect to the stone expulsion rates. Results No statistically significant difference was noted between all groups regarding the age, sex, or stone burden (p > 0.05). Spontaneous stone expulsion rates after 4 weeks were 64.8 %, 69.2 %, 75.7 %, and 26.4 % in group 1, 2, 3, and 4 respectively. Spontaneous passage rates were statistically higher in all treatment groups when compared with the control group. Despite the highest spontaneous stone expulsion rate noted in group 3; this difference was not statistically significant when compared with the group 1 and 2. No major side effect related to the medications was observed. Conclusions Tamsulosin facilitated the spontaneous passage of distal ureteral stones < 10 mm in size in an effective manner particularly when applied in combination with an oral corticosteroid.
Keywords: ureteral stone; tamsulosin; deflazacort; medical treatment; urolithiasis